Design and simulation of phase-shifted full bridge converter for hybrid energy systems - Ibrahim, O. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents design and Simulink implementation of zero voltage switching (ZVS) phase-shifted full bridge DC-DC converter. The phase-shifted full bridge PWM DC-DC converter is widely used in high power, high voltage applications due to the advantages of high power handling capability with low switching and conduction losses. The phase shift feature of the control signal allows ZVS thereby eliminating the switching losses during FET device transition. It also minimize the parasitic effect and conduction losses at high frequency operation thereby increase system efficiency. A 3kW, 100 kHz high frequency phase-shifted full bridge converter was design and simulated in Matlab/Simulink to analyze the system performance prior to experimental implantation. The converter is intended for hybrid energy systems (HES) application in which a state space controller will be developed with wider dynamics to accommodate variable input sources mostly from renewable energy resources like solar and wind power. The converter simulation results shows that the system achieved greater than 90 efficiency at full load current. © 2016 IEEE.